EFFECT OF “SITTAMATTI (SIDA CORDIFOLIA LINN.) KUDINEER (DECOCTION)” IN RESPIRATORY COMPLAINT - COUGH - Rajeev, S. R. Pholtan (International Journal of Research -GRANTHAALAYAH, 2020)
Background: The world is fulfilled by various medicinal plants which are widely have been used in treatment of various diseases since ancient time. Medicinal plants still play an important role in emerging and developing countries. Herbs are staging a comeback and herbal ‘renaissance’ is happening all over the globe. The herbal products today symbolize safety in contrast to the synthetics that are regarded as unsafe to human and environment. Although herbs had been priced for their medicinal, flavoring and aromatic qualities. In this research, sittamatti (Sida cordifolia) has been reported to possess analgesic, anti-inflammatory and hypoglycemic activities as well as hepato-protective activity. Traditionally the plant Sida cordifolia (Linn) has been used as CNS depressant, fat lose, analgesics, anti-inflammatory, hypotensive, hepato protective. Presence of ephedrine has highlighted the utility of this plant. various Ayurvedic preparation of this plant used in asthma diseases, etc. Methods: This plant spread in Mullaitivu commonly therefore utilize that as Cough decoction. First authentication of plant with experts from University of Jaffna and collecting, washing, drying and grinded for decoction preparation size. Then packing and labeling and distribute to selected 60 research samples of two groups to clinical trial and collected data through questionnaire and result analyzing in statistical way. Result: Group-I & Group-II 1st Week (AFTER treatment) level of the samples. The test is significant at 0.0001 (adjusted for ties) Comparing the HT (Group-I), Research Decoction (Group-II) was shown Significant (p<0.05) reduction in symptom of cough. One-month (04 Weeks) of treatment with research decoction significantly (p<0.05) change symptom of cough with the control group- hospital internal treatment (HT) (group-I). Conclusion: effectiveness of research drugs – Sittamati Kudineer, Three months (04 Weeks) of treatment with research decoction significantly (p<0.05) change symptom of cough with the control group- normal hospital internal treatment (HT) (group-I).